Factors Contributing to Length of Stay Prolongation among Emergency Room Patients during the Covid-19 Pandemic: A Study at Persada Hospital - Simanungkalit, Sylvia Kitty; Holipah, Holipah; Dewanto, Aryo; David, David (Fakultas Kedokteran Universitas Brawijaya, 2021)
Extended length of stay (LOS) in the Emergency Department (ED) results in crowding, potentially causing adverse events and patient dissatisfaction. The Covid-19 pandemic has forced hospitals to implement screening procedures that can extend the LOS of patients in the ED. This study aimed to provide an overview of changes in ED LOS during the pandemic and its contributing factors. This study used a descriptive approach through observation and interviews. LOS observations were conducted using the time & motion study method to determine the average time in each ED stage. The observation results identified the differences in the average LOS during the Covid-19 pandemic, which was 2 hours 39 minutes 52 seconds, and the longest time was on laboratory examination (2 hours 59 minutes 27 seconds). A lengthy laboratory examination duration is due to the additional laboratory examination procedure (serology) for SARS COV-2, suboptimal screening team, and the absence of notification in the hospital information system.